« N’oublie pas d’où tu viens ». La socialisation à l’attachement familial et transnational de descendant.es d’immigré.es malien.nes - Théoxane Camara (Enfances, Familles, Générations)
Research Framework: When, in the 1980s, Malian immigrant couples chose to settle in France, they found themselves caught up in a system of “mutilated kinship” caused by emigration (Barou, 1991). A veritable “work of kinship” (di Leonardo, 1987) is required to maintain links with relatives who have remained in Mali, and to pass on to children born and socialized in France a sense of belonging to the family group, despite the distance.Objectives: This article looks at how children born in France in the 1980s and mid-1990s are socialized to family and transnational ties during their childhood and preadolescence - i.e., before their first stays in Mali.Methodology: The 50 in-depth life story interviews conducted out with ten Malian immigrant families enable us to reconstruct family socialization universes in retrospect.Results: I show at first that the recounting of the parental past, more than intergenerational transmission of first names, constructs affiliation to the family line. I then highlight how parental practices of mutual aid and welcoming transnational relatives to France help accustom children to their future duty of transnational redistribution and solidarity. Finally, I outline the socializing effects of regular visits to migrant workers’ hostels, where male relatives reside, by highlighting the gendered dimension of this socialization.Conclusions: Through these three processes of family socialization, children learn gendered family and transnational roles, even if their boundaries are partly blurred by migration. Sons learn above all an economic sense of family (sending money to relatives in Mali and supporting the family in France), while daughters are more socialized to a matrimonial sense of the family (marrying a male Malian relative and perpetuating the lineage).Contribution: At the crossroads of the sociology of socialization, the family and migration, this text contributes to our knowledge of the ordinary life of immigrant and/or transnational families, by emphasizing the socializing effects of transnational family configurations and their gendered variations.